Theoretical insights into thermal transport and structural stability mechanisms of triaxial compressed methane hydrate - Chen, Dong-Sheng; Miao, Ting-Ting; Chang, Cheng; Guo, Xu-Yang; Guan, Meng-Yan; Ji, Zhong-Li (Chinese physics B, 2024)
The heat transfer and stability of methane hydrate in reservoirs have a direct impact on the drilling and production efficiency of hydrate resources, especially in complex stress environments caused by formation subsidence. In this study, we investigated the thermal transport and structural stability of methane hydrate under triaxial compression using molecular dynamics simulations. The results suggest that the thermal conductivity of methane hydrate increases with increasing compression strain. Two phonon transport mechanisms were identified as factors enhancing thermal conductivity. At low compressive strains, a low-frequency phonon transport channel was established due to the overlap of phonon vibration peaks between methane and water molecules. At high compressive strains, the filling of larger phonon bandgaps facilitated the opening of more phonon transport channels. Additionally, we found that a strain of −0.04 is a watershed point, where methane hydrate transitions from stable to unstable. Furthermore, a strain of −0.06 marks the threshold at which the diffusion capacities of methane and water molecules are at their peaks. At a higher strain of −0.08, the increased volume compression reduces the available space, limiting the diffusion ability of water and methane molecules within the hydrate. The synergistic effect of the strong diffusion ability and high probability of collision between atoms increases the thermal conductivity of hydrates during the unstable period compared to the stable period. Our findings offer valuable theoretical insights into the thermal conductivity and stability of methane hydrates in reservoir stress environments.